KONDISI DAN TINGKAT KERUSAKAN JALAN PADA JALAN JENDERAL SUDIRMAN KOTA AMBON - Lumalessil, Tirza; Purwanto, Hadi; Roberth, Herry Henry (Journal Agregate, 2024)
Roads are one element of land transportation which is intended to facilitate the movement of people or goods. If road damage occurs it can have an impact on social conditions, especially land transportation facilities. Many causes of road damage are caused by vehicle loads and vehicle volumes which continue to increase beyond road capacity.   The aim of this research is to determine the types of damage that occur on these road sections, such as potholes, longitudinal cracks, collapse, patching, and loose grain which is damage to the Jendral Sudirman road, Ambon City. Based on the level of damage or the condition of the road that has deteriorated, road damage will be handled according to the PCI method according to the level of road damage on the Jendral Sudirman road section, Ambon City.From the results of calculating the condition of the road pavement on Jalan Jendral Sudirman, Ambon City, a rating of 65% was obtained with the condition (Fair).